Pollution prevention for chemical processes - Allen, David T. (John wiley & Sons, Inc., 1997)
This timely text offers coverage of pollution prevention fundamentals, featuring examples and case studies drawn from the chemical process industries. Topics are presented on three different levels-macro, meso, and micro. The book's multifaceted approach provides a complete picture of current waste minimization theory and practice.